ROLE OF SPRAYING BORON AND SUGAR ALCOHOLS ON GROWTH, YIELD AND SEEDS PRODUCTION OF PEPPER - & Abdul Rasool, Mosleh (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this experiment was to investigate the effect of boron and sugar alcohols on the growth, yield and quantity of seeds produced from pepper cv. California wonder, A factorial experiment (3 × 7) was conducted according to randomized complete block design (RCBD) with three replications at the open field of the research station B, Coll. of Agri. Univ. of Baghdad during 20/12/2016 to 1/12/2017. The experiment included two factors, first one was boron which used boric acid (0, 50, 100 mg l -1) and the second factor was sugar alcohols (sorbitol) (15, 25, 35 g, l -1) and mannitol sugar (10, 20, and 30 g l -1) in addition to control treatment ( spraying with water), Results showed significant superiority of boron with concentration 100 mg l -1 in the plant high (58.60 cm), number of main branches plant-1 (7.52 branch), leaves area (1129.9 dcm2 plant-1), number of fruits plant-1 (49.43 fruit) and total yield (148.64 ton ha-1). Significant superiority of mannitol with concentration 30 mg l -1 was found in the plant height (60.34cm), number of main branches (7.33 branch plant-1), leaves area (1237.8 dcm2), total chlorophyll content (302.11 mg g-1 fresh weight), fruit weight (96.27 g fruit-1), number of fruits (50.84 fruit plant-1), total yield (158.39 ton ha-1) seeds germination (91.66%), speed of germination (4.67 day). The interaction between two variables was significant for all the studied traits, this showed that the response of pepper to first variable related to the other variable. It could be concluded that the best combination between two variable was boron (100 mg l-1) and sugar alcohols (mannitol 30 g l-1).